Hubungan antara Kadar Low Density Lipoprotein dengan Tekanan Darah Sistolik saat Puncak Exercise pada Personil Kepolisian Daerah Sulawesi Tenggara (The Relationship between Low Density Lipoprotein Levels and Systolic Blood Pressure during Peak Exercise of Police Personnel in Southeast Sulawesi) - Dina Fitriana; Hilma Yuniar; Jamaluddin Jamaluddin (Halu Oleo University, 2020)
Background: Systolic blood pressure during exercise is the blood pressure as measured by aneroid sphygmomanometer at the peak exercise (treadmill), namely when the subject has experienced fatigue or heart rate has reached > 85% of Maximum Heart Rate. Purpose:This research purpose is to determine the relationship between LDL level and systolic blood pressure at the exercise peak of police personnel in Southeast Sulawesi. Methods: This research used analytical-observasional study with cross sectional aproach. The independent variables used in this research are LDL level while the dependent variables was systolic blood pressure during the peak exercise. Research location is in Maxima Laboratory Kendari.The subjects of this study were 95 people based on the inclusion and exclusion criteria that selected by Purposive Sampling method. Data collection was gained by taking the secondary data and was processed by using statistical test data of Independent T-test with a significance p-value <0.05. Result: The result of bivariate analysis showed that there was a relationship between LDL level and systolic blood pressure at the exercise peak on the police personnel in Southeast Sulawesi with a p-value = 0,000 (<0.05). Conclusion: This study can be conlcuded that there was a relationship between LDL level and systolic blood pressure at the peak exercise of police personnel in Southeast Sulawesi.Keywords: low density lipoprotein, systolic blood pressure, peak exercise. ABSTRAKLatar belakang : Puncak tekanan darah sistolik pada saat exercise adalah tekanan darah sistolik yang diukur dengan menggunakan sfignomanometer air raksa pada saat puncak exercise, dimana subyek sudah mengalami kelelahan atau denyut jantung telah mencapai 85% dari denyut jantung maximal. Tujuan: Tujuan penelitian ini adalah untuk mengetahui hubungan antara kadar LDL plasma dengan tekanan darah sistolik pada puncak exercise pada personil Kepolisian Daerah Sulawesi Tenggara. Metode: penelitian ini merupakan penelitian analitik-observasional dengan metode cross sectional. variabel independen adalah kadar LDL plasma dan dependen variabel adalah tekanan darah sistol pada puncak exercise. penelitian dilakukan di Laboratorium Klinik Maxima Kendari. sebanyak 95 sampel penelitian yang memenuhi kriteria inklusi dan eksklusi diambil dengan metode purposive sampling. Data tekanan darah saat puncak exercise dan kadar LDL plasma diambil dari data sekunder rekam medik pasien. Data kemudian dianalisa dengan uji statistik Independent T-test dan bermakna bila nilai p <0,05. Hasil: Analisa statistik menunjukkan adanya hubungan antara kadar LDL plasma dengan tekanan darah sistolik pada puncak exercise pada personil POLDA Sulawesi Tenggara, dengan nilai p=0,000. Simpulan : Pada penelitian ini dapat disimpulkan bahwa terdapat hubungan antara kadar LDL plasma dengan tekanan darah sistolik pada puncak exercise pada personil POLDA Sulawesi Tenggara.Kata Kunci: low density lipoprotein, tekanan darah sistolik, puncak exercise